Assessing level of pre and post interventional knowledge and attitude for dengue awareness among selected government school student of Bhopal, India - Meena, J. S.; Mahore, Rajendra; Sahay, Abhishek; Sengar, S. S. (International Journal Of Community Medicine And Public Health, 2020)
Background: Dengue is a major public-health issue all over tropical and sub-tropical regions of the world. It is the most rapidly spreading mosquito-borne viral disease, which shows a 30-fold increase in global incidence over the past 50 years. According to the estimates from the World Health Organization 50-100 million dengue infections occur each year and that to add to the seriousness that around 50% of the world’s population lives in countries where the disease is endemic. Methods: Educational Interventional cross-sectional study done in 2 selected Govt. Higher Secondary School in Bhopal. 100 students were selected in both school in which 50 boys and 50 girl’s student selected. A pretested, semi-structured questionnaire developed by investigator which comprised of 36 questions. The interviewee who was willing to participate in the study was given the questionnaire and was asked to fill the questionnaire before and after the educational intervention and the results were analyzed. Results: The study involved a total of 100 students who successfully answered all the baseline and follow up questionnaire. A total of 50% male students and 50% female students were present in this study. This study showed of significance increase in knowledge and significance change in their attitude after the post intervention questionnaires. Conclusions: The knowledge about dengue fever was good among students, attitudes towards to keep their surroundings was also good; however, it was found that the good knowledge and attitudes does not necessarily lead to good practice. Health education programme should be continued and intensified with emphasis on school, college students and young adults.